A new Appenninic station of Dryomys nitedula Pallas, 1979 (Rodentia, Gliridae) / Nuova stazione appenninica di Dryomys nitedula (Pallas, 1779) (Rodentia, Gliridae) - Maria Grazia Filippucci (Hystrix, the Italian Journal of Mammalogy, 1986)
Abstract A new record of Dryomys nitedula from the massif of Pollino (Southern Italy) is given and the value of the subspecific division (D. nitedula intermedius, D. nitedula aspromontis) in Italy is discussed. Riassunto Viene segnalato il ritrovamento di un esemplare di Dryomys nitedula sul Massiccio del Pollino e ridiscusso il valore della ripartizione sottospecifica (D. nitedula intermedius, D. nitedula aspromontis) in Italia.